Outflow Through Aortic Side Branches Drives False Lumen Patency in Type B Aortic Dissection - Logghe, Gerlinde; Trachet, Bram; Segers, Patrick; De Backer, Julie; Mulorz, Joscha; Dueppers, Philip; Vermassen, Frank; Schelzig, Hubert; Van Herzeele, Isabelle; Wagenhäuser, Markus U. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD) aims to induce false lumen (FL) thrombosis by sealing the intimal tear between true (TL) and FL and blocking the inflow into the FL. Incomplete thrombosis of the FL is correlated with poor clinical outcome. We hypothesize that the number of major and minor branches emanating from the FL affect FL patency and may negatively influence TEVAR induced FL thrombosis. Methods: Computed tomography (CT)-scans from 89 patients diagnosed with TBAD (best medical treatment (BMT) n=52, TEVAR n=37) from two high-volume vascular surgery centres were analysed retrospectively. Analysis included evaluation of FL patency status along with the number, location and size of intimal tears and the presence of minor and major side branches originating from the FL. Multiple regression analysis was conducted to evaluate obtained parameters as predictors for FL thrombosis status. Results: In univariate analysis, the strongest correlation for FL patency was found for the number of major (R=0.79) and minor (R=0.86) side branches originating from the FL. When applying a multiple linear regression model, the number of major (normalized beta 0.37; P<0.001) and minor branches (normalized beta 0.41; P<0.01) emanating from the FL were valid predictors for the axial length of the patent and non-patent FL and additionally determined the length of the patent FL at 12-month follow-up in patients that underwent TEVAR. Conclusions: Our data suggest that the number of minor side branches that originate from the FL in TBAD is an important determinant of FL patency, to a greater degree than previously assumed.